Estimates of pesticide deposition by droplet size analysis - Chain, Aldemir; Maia, Aline Holanda Nunes; Pessoa, Maria Conceição Peres Young (Pesquisa Agropecuaria Brasileira, 1999)
The available methodologies for analysing the pesticide reaching the target are sophisticated or expensive. The objective of this work was to compare two methods to quantify the pesticide deposition. One of them by droplets analysis and the other by chemical tracer analysis. The droplets of a fungicide spray were sampled using water sensitive papers, slides with oxide magnesium and cards of filter paper. In the droplet analysis method, the volume of spray deposited on a delimited area was estimated considering the diameters of stains or craters, spread factors and droplet density. In the chemical tracer analysis method the volume was calculated by the residue deposited on sampling target and spray concentration. There were no statistic differences in the volumes estimated by the two methods.